The effect of integrated care on self-management and emergency department attendance. (13th February 2019) - Scheiner, Nikki; Cohen, Sarah; Davis, Ruth; Gale, Tim; Agyare, Amanda
Abstract : Aims and method: The Frequent Attenders Programme is a joint initiative between Hertfordshire Rapid Assessment, Interface and Discharge service and the Emergency Department of the West Hertfordshire NHS Trust, which aims to divert frequent attenders from the emergency department by addressing their unmet needs. This paper describes the range of interventions put in place from the time that the service was set up in 2014 until the introduction of the new national Commissioning for Quality and Innovation 2017–2019, which tasked National Health Service trusts to improve services for people with mental health needs who present to Accident and Emergency. The terms emergency department and Accident and Emergency are used interchangeably, reflecting the practice in policy documents. A subsequent article will report on the impact of the Commissioning for Quality and Innovation in Hertfordshire. Results: Analysis of the interventions indicated a highly significant ( P < 0.0001) mean reduction in attendances. Lower gains were made in patients whose primary presentations were alcohol-related. A failure to effect change in two patients led to a significant revision of their respective care plans, resulting in a subsequent reduction in their attendances. Clinical implications: An integrated approach to patients with complex presentations was associated with high levels of both patient and referrer satisfaction. It is hypothesised that dismantling the barriers between physical and mental health may lead to similar successes in frequent attenders in other in-patient and community medical and psychiatric services. Declaration of interest: None.